Território e territorialidades: dimensões constitutivas da relação homem e meio ambiente (Territory and territorialities: constitutive dimensions of the relationship between the man and the environment) - Morais, Hugo Arruda (Revista brasileira de geografia física, 2018)
Este artigo possui como objetivo central apresentar algumas questões teóricas referentes ao debate em torno do território e das territorialidades como dimensões constitutivas do homem com o meio ambiente. Como o território e as territorialidades são fruto da inter-relação e da interação entre atores sociais e o meio ambiente físico e social, as ideias apresentadas buscam colocar em destaque o papel desses dois conceitos como componentes para a compreensão de como a sociedade se organiza, como também, abrirá espaço para o debate em torno do papel dos sujeitos no controle de suas próprias ações referentes ao seu espaço de vida.  A B S T R A C T This article aims at presenting some theoretical questions concerning the debate around the territory and the territorialities as constitutive dimensions of the relationships between man and environment. As the territory and territorialities are the result of the interrelationships and interactions between social actors and the physical and social environment, the idea presented here is to highlight these two concepts as components for understanding how society is organized, but also will open space for the debate around the role of the subjects in the control of their own actions in their space. With regard to the methodology, we used hermeneutics procedure, especially because it is an important instrument for interpreting the content of the texts. The main result of this article is to present a theoretical perspective, from the Italian Geography, about the territory as a product of the social relationships established between the people in the process of appropriation of the environment. This allows us to understand the territorialities as a set of social practices for understanding the production and territorial disputes, allowing future studies concerning the territory and the territorialities. Keywords: active territoriality, territorial autonomy, environmental knowledge, italian geography.